Understanding the Thymic Microenvironment: the Cellular and Molecular Basis of T Cell Development (Central Asian Journal of Medical Sciences, 2016)
Objectives: The thymus is a primary lymphoid organ that provides specialized microenvironment for T cell development. A variety of thymic stromal cells form the thymic tissue architecture and critically regulate the development and repertoire selection of T cells. Methods: We reviewed historical and recent studies on thymic stromal cells, especially focusing on the well-characterized functions of thymic epithelial cells (TECs) and the significance of as yet less characterized non-TEC thymic stromal cells and hematopoietic antigen-presenting cells in the regulation of T cell development. Results: Cortical TECs (cTECs) induce positive selection of diverse and functional T cells, while medullary TECs (mTECs) establish T cell tolerance via the negative selection of auto-reactive T cells and their conversion into regulatory T cells. These modes of T cell tolerance induction are also mediated by hematopoietic antigen-presenting cells such as dendritic cells and thymic B cells. Thymic mesenchymal cells, a prominent component of non-TEC thymic stromal cells, support the development and maintenance of TECs and thereby T cell production. Conclusion: Understanding the cellular and molecular basis for thymic stromal subsets will provide invaluable information toward in vivo reconstitution of the thymic microenvironment for future therapeutic applications.